Prototype of Detector for Metal Content in Packaged Drinks Using Salinity Sensor Based on Arduino Uno - Mauliddin Mauliddin; Muhammad Daud; Teuku Multazam; Ainal Mardhiah; M. Fitra Waldi (Jurnal Teknologi, 2026)
This research aims to design and build a prototype device for detecting iron (Fe) and manganese (Mn) metals in packaged drinks using a salinity sensor processed using the Kalman filter method. Packaged drinks are a popular choice due to their convenience and variety of flavors, but their metal content needs to be monitored to prevent health risks. This system was designed using an Arduino Uno microcontroller as the main controller, with a salinity sensor to detect Fe and Mn levels, and an LCD as the data display. Testing was conducted by comparing the device's detection results with laboratory data obtained from the Banda Aceh Industrial Standardization and Services Center. The results showed that the device was able to detect Fe with an accuracy of 98.48% and Mn with an accuracy of 100%. The average measurement error for Fe was 1.52%, while for Mn, the error was 0%. These results demonstrate that the designed device functions well and has high accuracy, thus potentially being used as an independent test tool for the suitability of packaged drinks.